What educators could do to facilitate students' use of a deep approach to learning: A multisite cross-sectional design. (June 2020) - Takase, Miyuki; Niitani, Mayumi; Imai, Takiko
Abstract: Background: Despite the proliferation of diverse teaching methods, it is uncertain which teaching components have enhanced students' approach to learning and in what way these components have produced positive outcomes. Objectives: The aim of the study was to examine how the students' perceptions of learning activities, the acquisition of relevant knowledge, and educators' enthusiasm/supportive attitudes impact on the students' adoption of the deep approach to learning. Design: A multisite cross-sectional design. Settings: Two universities in Japan. Participants: Undergraduate nursing students (n = 154). Methods: Questionnaires, which included the Teaching Approach Scale and the Japanese version of the Learning Approach Scale, were given to the students. Data were analysed by path analysis. Results: The students' perceptions of learning activities were positively related to their use of a deep approach to learning. Moreover, this relationship was completely mediated by their perceptions of knowledge acquisition and educators' enthusiastic and supportive attitudes. Conclusions: The findings suggest that learning activities must be reinforced by appropriate educator support that enables students to acquire relevant knowledge and feel that learning is interesting and enjoyable. Without such support, interest and active engagement incurred by learning activities may quickly disappear, and learning activities may not lead to a change in the students' approach to learning. Highlights: Learning activities in class have the potential to promote students' learning. Providing relevant knowledge is also important for facilitating students' learning. Enthusiastic and supportive educators may turn students into active learners. Educators need to boost students' interest and engagement in learning.